HARLEY-DAVIDSON BRAND COMMUNITY CONSUMER BEHAVIOR AND THE INFLUENCE OF THE SELF-EXPANDED - Machado Santos, Edna de Souza; Silva, Dirceu da; Braga Junior, Sergio Silva [UNESP]; Xavier do Nascimento, Carlos Alberto (Univ Nove Julho, 2017)
This research aims to evaluate the influence of attitudes and desires on self-expanded on consumer behavior in the Harley-Davidson brand community. The relevance of this study points to the fact that brand communities represent a fundamental subject of study for marketing area in Brazil, for working conditions to investigate, in more depth, an understanding about the influence and type of culture that Brazilian consumers do not refer to brand equity (Atkin, 2007; Yoo& Donthu, 2001; Aaker, 1998). The research corpus counted with a survey with 193 participants of communities of mark. The methodological approach was quantitative with the use of SmartPLS data for data analysis. The results obtained demonstrate that intergroup relationships about positive attitudes, desires and emotions are shared feelings that broaden the desire to participate in the activities of the brand community, culminating in an expansion of the self of the member of Harley-Davidson community, with group behavior, social interaction, involving social identity and behavior towards a brand.
Keywords: Brand Community; Social Identification; Harley-Davidson; Self-Expanded